Finger peripheral resistance during local cold provocation in vasospastic disease. - Pyykko, I.; Kolari, P.; Farkkila, Markus; Starck, Jukka; Korhonen, Olli; Jantti, V. (Scandinavian Journal of Work, Environment & Health, 1986)
Finger systolic blood pressure (FSBP), finger arterial inflow (FAI), finger venous opening pressure (FVOP), and finger peripheral resistance (FPR) were evaluated in 56 workers exposed to chain-saw vibration. Twenty-one of the workers were free from vibration-induced white finger (VWF). In 17 subjects VWF had ceased; 12 of the subjects had active VWF; 6 subjects had Raynaud's disease. The subjects were examined in a supine position under thermoneutral conditions with strain-gauge plethysmography. Cold provocation of the finger caused a significant reduction in FSBP in the groups with Raynaud's disease and active VWF. The finger circulation of the subjects with active VWF and that of those with Raynaud's disease showed a significantly reduced FAI when compared with that of the symptom-free referents. Finger cooling produced a gradual reduction in the FVOP and a significantly increased FPR of the subjects with active VWF and in those with Raynaud's disease. FPR was already increased in the Raynaud's disease group at the beginning of the test, whereas it increased in the VWF group as the temperature fell. The results suggest that in Raynaud's disease the fault is in the level of activity of the sympathetic outflow and in VWF it is peripheral mechanisms controlling the vessel tone.